El bloque de constitucionalidad - Del rosario Rodríguez, Marcos (Revista de Derecho, 2019)
The constitutionality block from its origins, either from a perspective regulatory or substantial perspective, has emerged as a determinant of the task space state supreme recently in favor of human rights, especially the pro persona principle. That is why for adequate protection of this principle, as well as the operation of the fuzzy control of conventionality, requires the existence of the constitutional for a better cause and efficacy to the effectiveness of human rights.